Bioconversion of environmentally hazardous plants by anaerobic microbiome with detoxification of heavy metals and methane production - Tymoshenko, Artem; Kyrylov, Semen; Yastremska, Larysa; Bida, Iryna; Havryliuk, Olesia; Hovorukha, Vira; Tashyriev, Oleksandr (Problems of Environmental Biotechnology, 2024)
The aim of the work is to investigate the process of bioconversion of environmentally hazardous plants by anaerobic methanogenic microbiome with simultaneous detoxification of heavy metals and methane production